Three views on the millennium and beyond - Blaising, Craig A.; Gentry, Kenneth L.; Strimple, Robert B., 1935-; Bock, Darrell L. (Grand Rapids, Mich. : Zondervan, 1999)
Are these the last days? Could Jesus return at any time to establish his thousand-year reign on Earth? What is the nature of Christ's millennial kingdom referred to in the book of Revelation? What must happen before Jesus returns, and what part does the church play? Three predominant views held by evangelicals seek to answer these and related questions: premillennial, postmillennial, and amillennial. This book gives each view a forum for presentation, critique, and defense. Besides each contributor's personal perspective, various interpretations of the different positions are discussed in the essays. The Counterpoints series provides a forum for comparison and critique of different views (both Christian and non-Christian) on important theological issues.
Editor's preface / Darrell Bock -- 1. Postmillennialism / Kenneth L. Gentry, Jr. -- Responses / Robert B. Strimple, Craig A. Blaising -- 2. Amillennialism / Robert B. Strimple -- Responses / Kenneth L. Gentry, Jr., Craig A. Blaising -- 3. Premillennialism / Craig A. Blaising -- Responses / Kenneth L. Gentry, Jr., Robert B. Strimple -- Summary essay / Darrell L. Bock.
Includes bibliographical references (p. 311-316) and index.
Keywords: Millennialism -- Comparative studies